Dynamic Mitochondrial Proteome Under Polyamines Treatment in Cardiac Aging - Zhang, Hao; Yan, Meng; Liu, Ting; Wei, Peiling; Chai, Nannan; Li, Lingxu; Wang, Junying; Yu, Xue; Lin, Yan; Qiu, Bintao; Zhao, Yajun (Frontiers in Cell and Developmental Biology, 2022)
Age-related alteration of mitochondria causes impaired cardiac function, along with cellular and molecular changes. Polyamines can extend life span in mice. However, whether polyamines can affect the dynamic mitochondrial proteome, thereby preventing aged-related changes in cardiac function and cardiac aging remains unclear. In this study, we found that spermine (Spm) and spermidine (Spd) administration for 6 weeks could prevent 24-month old rats heart dysfunction，improve mitochondrial function and down-regulate apoptosis. Using iTRAQ tools, we identify 75 mitochondrial proteins of statistically significant alteration in aging hearts, which mainly participate in important mitochondrial physiological activity, such as metabolism, translation, transport, apoptosis and oxidative phosphorylation. Moreover, four proteins of differential expression, pyruvate dehydrogenase kinase (PDK4), trifunctional enzyme subunit alpha (HADHA), nicotinamide nucleotide transhydrogenase (NNT) and Annexin6, which were significantly associated with heart aging, were validated by Western Blotting. In vitro, we further demonstrated polyamines could retard cardiomyocytes aging through down-regulating the expression of PDK4 and thereby inhibiting cell apoptosis. In summary, the distinct mitochondrial proteins identified in this study suggested some candidates involved to the anti-aging of heart after polyamines treatment, and PDK4 may provide molecular clues for polyamines to inhibit apoptosis and thus retarding aging-induced cardiac dysfunction.